Konstruksi Identitas Kedaerahan oleh Media Massa Lokal - Putri Aiysiyah Rachma Dewi (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2011)
This article focuses on how the local print media view of regional identity artists involved in the video contained sexual scenes. The author raised the case of video sexual scenes involving Ariel, Luna Maya, and Cut Tari. All three are national artist when the video was circulated in the society. The three newspapers under study are the Bali Post, Serambi Indonesia, and Pikiran Rakyat. The results showed that the three newspapers was to discredit the three artists with the construction of such news. The newspaper did not give chance for artists to express their opinions.